Efficacy of Lactobacillus plantarum 1582-Fermented Chive (Allium schoenoprasum) as a Natural Antibiotic Against Eimeria acervulina in Broiler Chicken - Hai, P. V.; Dung, H. T.; Hung, P. H. S. (Faculty of Animal Science, IPB University, 2025)
This study evaluated the efficacy of chive (Allium schoenoprasum) fermented by Lactobacillus plantarum 1582 (FC) as an antibiotic alternative in controlling Eimeria acervulina infection in broiler chickens. A total of 250 J-Dabaco male chickens were divided into five treatment groups, each with five replicates (cages) of 10 chickens: PC - positive control, NC - negative control, FC1 - supplemented with 1% FC, FC3 - supplemented with 3% FC, and antibiotic treatment (AB). Chickens in the NC, FC1, FC3, and AB groups were experimentally infected with E. acervulina at 14 days of age and monitored until day 42. Assessed variables included growth performance (body weight gain (BWG), feed intake (FI), feed conversion ratio (FCR), survival rate (SR), production efficiency index (PEI), serum immunoglobulins (IgA, IgM, IgG), ileal mRNA expression of tight junction (ZO-1, Claudin-2) and immune-related genes (IL-4, TNF-α, IFN-γ), fecal oocyst counts, and intestinal lesion scores. The results showed that both FC3 and FC1 groups improved BWG, FI, FCR, SR, and PEI, with the FC3 group showing the best performance, equivalent to the AB group. Additionally, FC contributed to preserving the integrity of the intestinal epithelium by enhancing tight junction protein expression (ZO-1, Claudin-2) and reducing inflammatory responses (IFN-γ, TNF-α), as well as reinforcing the intestinal barrier by improving villus morphology and reducing intestinal mucosal damage scores. Moreover, a significant reduction in Eimeria oocyst counts in the excretion demonstrated effective parasite control. These findings suggest that FC, especially at 3% concentration, can be an effective alternative to antibiotics in broiler farming for controlling coccidiosis and improving the safety and sustainability of production.